Acute hepatitis C infection after sexual exposure. Issue 1 (January 1995) - Healey, C J; Smith, D B; Walker, J L; Holmes, E C; Fleming, K A; Chapman, R W; Simmonds, P
Abstract : A case is described of a woman with acute hepatitis C infection whose partner had chronic hepatitis C infection and where heterosexual contact was the only major risk factor. Infection of both partners was confirmed serologically and by the finding of virus RNA by reverse transcription and polymerase chain reaction amplification. Nucleotide sequence analysis of the NS5 region (RNA polymerase) was used to show that both partners were infected with virus of the same genotype (1a). The nucleotide sequence of virus RNA found in the female patient is closest to variants cocirculating in the male contact, consistent with transmission having occurred between the two.